1973
DOI: 10.1111/j.1479-828x.1973.tb02297.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Symphysiotomy — Time for a Reappraisal?

Abstract: A series of 138 patients in whom symphysiotomy had been performed is presented. The vicissitudes of this operation are reviewed and an evaluation has been attempted of its role in the management of moderate disproportion. Early and late complications were few and rarely serious if recommended guidelines were adhered to.In the 200 years since symphysiotomy was repeat Caesarean sections. The next stage in first performed it has provoked considerable the operation's rehabilitation occurred about emotion amongst o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In countries where mortality from caesarean section is low, such as high‐income countries with current standards of obstetric care, symphysiotomy may be obsolete . Even at the peak of the popularity of symphysiotomy, it was not widely used in Britain and North America …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In countries where mortality from caesarean section is low, such as high‐income countries with current standards of obstetric care, symphysiotomy may be obsolete . Even at the peak of the popularity of symphysiotomy, it was not widely used in Britain and North America …”
Section: Discussionmentioning
confidence: 99%
“…25 Even at the peak of the popularity of symphysiotomy, it was not widely used in Britain and North America. 26 In the absence of randomised data, a Cochrane review 27 concluded that research was needed to provide robust evidence on the effectiveness and safety of symphysiotomy compared with caesarean section in clinical situations in which the risks and benefits are uncertain. One systematic review 12 of retrospective case series concluded that with training, symphysiotomy poses no greater risks and compares favourably with caesarean section, in terms of risk for the mother's life.…”
Section: Discussionmentioning
confidence: 99%